A Mouse Model of Furosemide‐Induced Overactive Bladder. Issue 1 (16th September 2016) - Saporito, Michael S.; Zuvich, Eva; DiCamillo, Amy
Abstract: Detailed in this unit is a mouse model of overactive bladder and urinary incontinence based on diuretic stress‐induced urination. The procedure involves the use of a unique, highly sensitive, and automated urine capturing method to measure urinary latency, frequency, and void volume. Although this method was first described and validated using an anti‐muscarinic drug used for treating overactive bladder, subsequent work has shown that effective non‐cholinergic agents can be detected. These findings indicate good predictive value for this model regarding the possible clinical utility of test agents as treatments for overactive bladder, regardless of their site of action. © 2016 by John Wiley & Sons, Inc.